Image analysis of Camelina sativa (Camelina sativa) seeds produced under micronutrient foliar treatment and its effect on germination percentage and speed - Sahar Rahmani; R. Tavakkol Afshari; Soroor Khorramdel; Seyyed Hossein Neamati (علوم و فناوری بذر ایران, 2024)
Camelina (Camelina sativa) is an important oilseed crop from the Brassicaceae family. This plant is important due to its industrial, health and food applications, and the cultivated area of this product is increasing, and important features of this plant. It can be attributed to the low need of this plant for inputs and high resistance to biotic and abiotic stresses. A factorial experiment in the form of a complete block design using SAS statistical software of the seeds of two varieties of Camelina (Sohail and Line 69) in terms of the effect of foliar spraying of micronutrients iron, zinc, manganese and the combined treatment and the control treatment immediately after closing After the formation of 50% of the seeds, foliar spraying was done and it was investigated during 3 repetition. The images prepared from Camelina plant embryos were evaluated and checked and the results of image analysis were compared with the results of the germination . The results of this experiment showed that the seed of line 69, which had the minimum cotyledon length, the minimum embryonic axis length, the minimum seed length and the maximum seed width in the combined foliar spraying treatment, had the minimum ratio of the embryonic axis length to the seed length, the minimum cotyledon length ratio It is related to the seed length and the minimum seed length to width ratio that the smaller size of the seed in line 69 has led to a decrease in the percentage and speed of germination .